2021
DOI: 10.3389/fmolb.2021.697586
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Peptides Targeting PPI in Clinical Development: Overview, Mechanism of Action and Perspectives

Abstract: Targeting protein-protein interactions (PPIs) has been recently recognized as an emerging therapeutic approach for several diseases. Up today, more than half a million PPI dysregulations have been found to be involved in pathological events. The dynamic nature of these processes and the involvement of large protein surfaces discouraged anyway the scientific community in considering them promising therapeutic targets. More recently peptide drugs received renewed attention since drug discovery has offered a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 124 publications
0
57
0
Order By: Relevance
“…It is in marked contrast with the total number of clinically significant PPIs whose interface can be modulated by drugs. In the analytical review by Cabri and co-authors [ 142 ], there were found 58 therapeutic peptides that occurred in CT’s reports. Of these, 13, 26 and 15 are in phase I, II and III, respectively, and 4 peptides are close to FDA approval (BBT-401, Foxy-5, Nangibotide and Reltecimod) [ 142 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in marked contrast with the total number of clinically significant PPIs whose interface can be modulated by drugs. In the analytical review by Cabri and co-authors [ 142 ], there were found 58 therapeutic peptides that occurred in CT’s reports. Of these, 13, 26 and 15 are in phase I, II and III, respectively, and 4 peptides are close to FDA approval (BBT-401, Foxy-5, Nangibotide and Reltecimod) [ 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the analytical review by Cabri and co-authors [ 142 ], there were found 58 therapeutic peptides that occurred in CT’s reports. Of these, 13, 26 and 15 are in phase I, II and III, respectively, and 4 peptides are close to FDA approval (BBT-401, Foxy-5, Nangibotide and Reltecimod) [ 142 ]. The first trial with 71 enrolled participants studied ALRN-6924 formulation containing the peptide inhibitor of MDM2/p53 for tumors with the wild-type TP53 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of peptides entering clinical trials year by year indicates that there is a growing interest from the side of pharmaceutical companies in the use of this class of molecules as drugs [ 14 , 15 , 16 ]. To date, the number of therapeutic peptides approved is 70 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first peptide used in treating disease was the hormone insulin in the 1920s [2,5,6]. Since then, peptide-based drugs have played a crucial role in clinical practice.…”
Section: Introductionmentioning
confidence: 99%